Literature Review: Effect of Pegagan Embun (Hydrocotyle sibthorpioides Lam.) Extract on NK and CD8 Cell Activity - Gusriyani, Sri; Aldi, Yufri; Umar, Salman; Afriwardi, Afriwardi (JURNAL PROTEKSI KESEHATAN, 2023)
There have been many traditional plants used for treatment, one plant that is widely used by the community for treatment is Hydrocotile sibthorpioides L. which is efficacious as an immunomodulator. In this plant, there are flavonoid compounds, namely rutin which has activity to increase the body's immune system, especially in NK and CD8 cells. NK (Natural Killer) and CD8 (Cluster of Differentiation 8) cells are components of the immune system that play an important role in immunomodulatory activity. This article review was conducted to obtain information on the effect of Hydrocotile sibthorpioides L. extract on NK and CD8 cell activity in the body. The writing method in making this research article review is comparative, which is taken from a collection of national journals and international journals. Various research results that have been obtained state that Hydrocotile sibthorpioides L. extract can affect the activity of NK and CD8 cells in improving the immune system.